Parameters study on the fabrication of Nickel-Titanium Shape Memory Alloy Core-Sheath Friction Yarn (NiTi-SMA CSFY) via DREF spinning machine / Mohammad Harris M. Yahya - M. Yahya, Mohammad Harris (Institute of Graduate Studies, UiTM, 2016)
The research focuses on the fabrication, mechanical and actuation performances of Nickel-Titanium Shape Memory Alloy Core-Sheath Friction Yarn (NiTi-SMA CSFY) produced from a DREF 3000 friction spinning machine parameters including spinning drum speed, delivery speed, core-sheath ratio and air-suction pressure. Two types of thin NiTi- SMA wires (SMA MEMRY wire and FLEXINOL Actuator wire) were used as the core of the yarn. Both 100% cotton and polypropylene (PP) fibers were used as the sheath and core fibers respectively. The selected machine parameters were arranged and categorised into several machine parameter plans. The first plan was focused on the determination of the appropriate yarn size to be spun the core-sheath yarn on the DREF 3000 friction spinning machine. The second plan was arranged to investigate the NiTi-SMA CSFY yarn mechanical properties. The third plan was arranged to validate the NiTi-SMA CSFY yarn actuation performance upon the parameters changes, in specific, the spinning drum speed, delivery speed and air-suction pressure. The appropriate Tex value was found to be 320 Tex as it was successfully spun the NiTi-SMA CSFY yarn without caused of machine stoppages…